Ethical considerations in zoological field research (Zoological Records and Reviews, 2025)
Zoological field research involves direct interaction with wild animals and their habitats, raising ethical obligations thatspan animal welfare, ecological impact minimisation, cultural sensitivity, and research integrity. Despite the existence ofregulatory frameworks -- including EU Directive 2010/63/EU on the protection of animals used for scientific purposes,national animal experimentation acts, and institutional ethics review committees -- significant inconsistencies in ethicalstandards, reporting practices, and oversight quality persist across European zoological research institutions. This reviewsynthesises evidence from 164 primary studies and institutional analyses (2005-2025) examining ethical practice,regulatory compliance, and animal welfare outcomes in European zoological field research. We evaluate five majorethical domains -- animal welfare and the Three Rs (Replacement, Reduction, Refinement), ecological impact ofresearch activities, informed community consent and Indigenous knowledge, data integrity and reproducibility, andwildlife crime prevention in research contexts -- against standards derived from EU Directive 2010/63/EU, the ARRIVEguidelines, and the International Society for Zoological Sciences code of ethics. A systematic audit of 280 zoological fieldstudies published 2020-2024 found that 58.4% did not report ethical approval source, 44.8% did not report capture andhandling protocols, and 38.4% did not justify sample sizes relative to welfare trade-offs. Practical standards for ethicalzoological field research reporting are developed, alongside a tiered risk assessment framework for field procedurewelfare classification aligned with EU Directive severity categories.
Keywords: ethical reporting; research integrity; ecological impact; zoology; field research; ARRIVE guidelines; EU Directive 2010/63/EU; Three Rs; animal welfare; research ethics